Growing vegetables and flowering plants in a greenhouse supplied with swine-building exhaust air. - Greig, J.K.; Spillman, C.K.; Koch, B.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Exhaust air from a Kansas State University swine-finishing house provides C02 and possibly other gases that are being used by vegetable plants in a KSU green house. In addition, a rock-storage system reduces fuel requirements of the greenhouse. Tomatoes and cucumbers have been the major food crops studied, but transplant production of geraniums, marigolds, snapdragons, and calendula also has been studied. Poinsettias were grown as a fall crop in 1980.
Keywords: Swine; Vegetables; Flowering plants; Greenhouse; Exhaust air